Contemporary Mosque Architecture in Egypt and Iran (a Comparative Analysis) - Ali, Hosam (AUC Knowledge Fountain, 2021)
I would like to introduce my research with this quote from Ahmed Hamid’s book Hassan Fathy and Continuity in Islamic Art and Architecture: As a student of Architecture at Cairo University’s Faculty of Engineering, I was ashamed that we Egyptians and Muslims had nothing in our syllabi that could be considered comparable to the genius of the west. Islamic architecture was omitted from the curriculum as being of no interest value for modern architects. It bothered me when I found that Egyptians believed the image propagated by some orientalists that Islam, and by implication its art and architecture, was backward.1 What is Islamic architecture in the first place? Rabbat summed Grabar’s words by stating that "Islamic architecture is the architecture built by Muslims, for Muslims, or in an Islamic country, or in places where Muslims have an opportunity to express their cultural independence in architecture."2 Therefore, no matter what the architecture looks like, no matter what statement it carries, it will still be Islamic as long as it satisfies these. This gives a wide spectrum of options in the design of Islamic architecture. Nevertheless, Islamic architecture is not a separate entity. It is a reflection and a vessel of Islamic culture in the place where it is situated. To trace the influences of Islamic culture on its architecture, it is important to emphasize two factors that regulate all aspects of life for Muslims, including the ways they construct or alter their environment. First, Islam tolerates cultural and aesthetical differences in a multitude of nations. The concept of tolerance is commanded in the Quranic verse 34:27: “We did not send you (Prophet Muhammad) for all mankind except to bring them glad tidings.” This means that the message of Islam is the message of acceptance of all the mankind with their differences in mindsets and cultures. When tolerance is applied to architecture it accommodates a cultural variety. Such cultural interactions and influences are evident when comparing Timurid architecture to Mamluk architecture, for example. Second, Islam urges us to respect the environment and be conscientious when altering it. For instance, the Prophet Muhammad used to consult all his fellows - even non-Arabs – when taking a decision on modifying spaces, as in the famous incident of digging trenches around the city following the advice of an Iranian, which was an innovative solution for the Arabs who had not previously known the concept of trenches. Despite such freedom of expression, the mosque remains the pivotal component of both Islamic identity and Islamic architecture. The belief for a Muslim is the core of life; therefore, the mosque becomes the center of their constructed environment. As Saoud (2002) puts it, “The religious beliefs and practices formed the center of cultural life for those populations, thus giving the mosque the central position in spatial and institutional hierarchies.”3 From a praying space built adjacent to the Prophet’s house from local simple materials, like mud bricks and palm tree trunks, to huge structures with extensive decoration and intricate components ‒ a mosque is the journey of the Muslim prayer space. “Today, people use a mosque only for the purpose of Ibadah. But we realize that Network of Mosques (NoM) has a great potential to improve social welfare for the society who live around the mosque.”4 Hence, studying the mosque is essential to understanding Islamic architecture. Another factor that has determined the face of Islamic architecture - and mosques, in particular - is related to socioeconomic changes in the world. The industrial revolution, modernism and postmodernism played a key role in changing the designs of mosques. This is reflected in the comment that the master jury of Aga Khan Award made about the Niono Mosque in Mali: "Islamic culture has only recently begun to emerge from a past whose aesthetic values were based on craft toward a future whose aesthetic values will surely be based on machine production."5 Islamic architecture comes in an abundance of manifestations. Various cultural and contextual influences on Islamic architecture continue to evolve. Throughout history Islamic architecture adopted the effects of surrounding architecture through adding spaces and elements that fitted the needs of the users. Nowadays, the concept is still the same, but there is more complexity to it, not only in the architecture itself, but also in the perception of architecture. Yet, with the rise of “the international style” and globalization since the mid-twentieth century, Islamic architecture has faced confusing choices for both users and architects posing the following questions. Should architects advocate their attachment to a particular historical period? Conversely, should they move on and adapt contemporary concepts and forms inspired by international architectural movements? Does the vocabulary of the past guarantee authenticity? Does the authenticity of this style of architecture merely depend on its forms and vocabulary? Does authenticity lie in the connection between a style and religious concepts? Many scholars, including Nasser Rabbat and Ali Gabr, tackled these questions studying multiple cases, especially following the debates around modernism, deconstructivism, traditionalism and regionalism since the mid twentieth century. My research will involve a summary of all these theories and their application in contemporary (21st century) Islamic architecture in Egypt and Iran. The purpose of this dissertation is to compare the approaches taken in both countries in designing mosques. My analysis will be based on the socio-political context of architecture, the influences that affected its designs and the lens of the relevant theoretical framework.